Medium- and Short-Chain L-3-Hydroxyl-Acetyl-Coenzyme A Deficiency: A New Identified Mutation in Four Cases. (11th September 2019) - Feng, Sheng; Cooper, Deborah; Tan, Lu; Meyers, Gail; Bennett, Michael
Abstract: Medium- and short-chain L-3-hydroxyacyl-coenzyme A dehydrogenase (M/SCHAD, SCHAD) deficiency is a mitochondrial fatty acid oxidation disorder (FAOD). This enzyme catalyzes the penultimate step in fatty acid oxidation, the NAD+ dependent conversion of L-3-hydroxyacyl-CoA to 3-ketoacyl-CoA for medium- and short-chain acyl-CoA intermediates (C4-C12). The clinical presentations of most patients are recurrent hypoglycemia associated with hyperinsulinism. We presented four infants with C4 acyl-carnitine elevation identified by newborn screening that also showed an unusual phenotype of congenital hypotonia and gross developmental delay. Enzymatic studies confirmed the disease. Sequencing analysis of all the HADH coding exons on the four patients revealed a homozygous variant of a novel change (c.908G>T, p.Gly303Val). Western blot analysis subsequently confirmed the lack of the SCHAD protein. In addition, there is another previously reported benign variant (c.257T>C) identified in three infants. Therefore, we postulate that the HADH variant (c.908G>T) is indeed pathogenic and associated with a severe phenotype as evidenced by the cases described herein. Population screening for the c.908G>T mutation suggests this mutation to be common among Puerto Ricans. We recommend that SCHAD deficiency is included as part of the differential diagnosis of all infants with congenital hypotonia.